T-cell receptor V beta expression in normal human skin. - Dunn, D A (1993)
The skin-associated immune system is the first line of defense against pathogenic attack from the environment and is simultaneously tolerant to localized autoantigens and to antigens of the normal microbial flora. The T-cell receptor (TCR) repertoire of skin lymphocytes may therefore be influenced by the skin microenvironment. We studied the expression of TCR beta-chain variable region (V beta) genes in normal skin by a polymerase chain reaction-based comparative method. When comparing the amplification of V beta genes in peripheral blood and normal skin, we found that TCR V beta 1, -7, -14, and -16 were often highly expressed in skin relative to peripheral blood, whereas V beta 5.1 was often highly expressed in peripheral blood mononuclear cells but not in skin. These results demonstrate that the TCR repertoire of skin lymphocytes is not determined by random sampling of peripheral blood mononuclear cells but may be molded by the interaction with self antigens and/or the normal microbial flora in the microenvironment of the skin.